Effect of chemical and enzymatic modifications on the identity characteristics of lard: a review - Marikkar, Jalaldeen Mohammed Nazrim; Abdul Manaf, Yanty Noorzianna (Taylor & Francis, 2014)
Lard is a fat substance extracted from the adipose tissues of swine. Due to its specific physical and functional characteristics, lard has found numerous uses in the food and feed industry. Lard has often been subjected to modification through techniques, such as fractionation, partial hydrogenation, and interesterification. Although the application range of lard in food would have widened, these modification techniques could also change the original identity characteristic properties of lard, which enable its detection in food by various analytical methods. The purpose of this review is to present an update of the current literature in this topic and provide some directions for future research.